The COVID-19 temptation?: Sino-Gulf relations and autocratic linkages in times of a global pandemic 1 - Demmelhuber, Thomas; Gurol-Haller, Julia; Zumbrägel, Tobias (The MENA region and COVID-19, 2022)
During the past decade, the increasing density of links between authoritarian countries has entered scholarly and public debate. There is evidence that the COVID-19 pandemic acts as a booster for processes of global autocratisation, differentiated by mechanisms such as autocratic promotion, diffusion or cooperation. The chapter examines the dynamics, mechanisms and implications of the pandemic against the backdrop of transregional autocratic practices. We argue that these are particularly observable in the relationship between China and the Arab Gulf states. Drawing on media reports and policy documents, the chapter analyses how different autocratic practices, measures and narratives diffuse across the region, along the example of four countries: the United Arab Emirates, Bahrain, Saudi Arabia and Oman. The chapter concludes by discussing the implications of the findings for future Sino-Gulf relations beyond the coronavirus pandemic.